Does Granting Refugee Status to Family-Reunified Women Improve Their Integration? - Linea Hasager (Center for Economic Studies and ifo Institute (CESifo), 2023)
In most countries, men are the principal asylum applicants, while women are admitted through family-reunification procedures. Family reunification implies that women's residence permits are contingent on remaining married to their husbands. Using a staggered Difference-in-Differences (DID) Design, I document that granting asylum to family-reunified women improves their economic integration, increases the probability of divorce and decreases their risk of being victims of violence. I find significant impacts on victimization and economic integration regardless of whether the woman remains married or not. I propose that the results can be explained by a reduction in uncertainty about residency and an increase in female bargaining power when the women are granted an autonomous asylum status.
Keywords: J12; J15; J61; K37; 330; refugees; asylum recognition; family reunification; female integration; violence against women; staggered difference-in-differences design